Self - Actualization in Sahar Mustafah's the beauty of your Face : Humanistic psychological perspective - Bunga Maharani Rozqi Rinonce (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1